Analisis Faktor-Faktor Yang Mempengaruhi Tax Avoidance - Hasanah, Neneng (Politeknik Raflesia Press, 2024)
This research aims to examine the factors that influence Tax Avoidance, That Factors Are Transfer Pricing and Sales Growth. This research is a type of quantitative research using secondary data. The sample in this research was 91 Property and Real Estate companies listed on the Indonesia Stock Exchange in 2019 - 2022. The method used was purposive sampling. Based on the purposive sampling method, the number of samples in this study was 28 selected companies. The research period was 4 years, so the resulting data was 112 samples. Hypothesis testing uses panel data testing with the help of the Eviews version 10 program. The panel data analysis model chosen in this research is the Random Effect Model. Based on the results of the partial test (t test) it can be seen that the Transfer Pricing and Sales Growth variables have no effect on Tax Avoidance.